2015
DOI: 10.1038/onc.2015.205
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotency factor Nanog is tumorigenic by deregulating DNA damage response in somatic cells

Abstract: The pluripotency gene Nanog is not expressed in normal adult tissues but is overexpressed in some human cancers. However, the tumorigenic roles of Nanog remain unclear. The ectopic expression of Nanog is not sufficient to induce spontaneous tumors in mice but can promote metastasis of established tumors by activating the expression of metastatic genes. The expression of Nanog in mouse skin activates tumor suppressor p53, leading to the differentiation of epidermal stem cells. In the absence of p53, Nanog induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…A causal role of NANOG in tumorigenesis has been demonstrated not only by loss- and gain-of-function studies in cancer cells [1, 3, 9] but also by, recently, CRISPR/Cas9-mediated knockout [31] and genetic mouse model [28, 32, 33,34] studies. In addition to constitutive expression of NANOG in a small subset of cancer cells, NANOG may also be induced by tumor microenvironments such as inflammatory cytokines and hypoxia [27, 30, 35].…”
Section: Discussionmentioning
confidence: 99%
“…A causal role of NANOG in tumorigenesis has been demonstrated not only by loss- and gain-of-function studies in cancer cells [1, 3, 9] but also by, recently, CRISPR/Cas9-mediated knockout [31] and genetic mouse model [28, 32, 33,34] studies. In addition to constitutive expression of NANOG in a small subset of cancer cells, NANOG may also be induced by tumor microenvironments such as inflammatory cytokines and hypoxia [27, 30, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Glycolysis is important to maintain the pluripotency, and the metabolic switch from glycolysis to oxidative phosphorylation is required for ESC differentiation . Accumulating evidence has suggested that pluripotency factors such as NANOG, OCT4, and SALL4 play important roles in maintaining glycolysis and genomic stability in ESCs . In this study, we identify IDO1 as a key regulator of pluripotency and metabolism in hESCs.…”
Section: Discussionmentioning
confidence: 78%
“…Consistent with previous findings, the expression of Nanog in skin cells activates tumor suppressor p53, leading to suppression of the oncogenic activity of Nanog. 9 In addition, hair follicle stem cells were depleted while there was an increase in epidermal differentiation markers. 9 It seems that Nanog-expressing stem cells, which can be potential tumor initiation (stem) cells, are removed by differentiation in both cases.…”
mentioning
confidence: 99%
“…9 In addition, hair follicle stem cells were depleted while there was an increase in epidermal differentiation markers. 9 It seems that Nanog-expressing stem cells, which can be potential tumor initiation (stem) cells, are removed by differentiation in both cases. This Nanog-induced differentiation could inhibit initiation of the 2-stage skin tumorigenesis observed in previous studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation